An Analysis of the Wake of Pedalling Cyclists in a Tandem Formation. (2016) - Barry, Nathan; Burton, David; Sheridan, John; Thompson, Mark; Brown, Nicholas A.T.
Abstract: Aerodynamics is a critical factor in the performance of cyclists, with drag being the dominant resistive force at racing speeds. Many cycling events involve athletes riding in close proximity. Previous studies have shown that flow interactions result in significant drag reductions for tandem cyclists, inline parallel to the flow[1–5] . However, the flow mechanisms associated with these changes have not been well characterised to date. This paper reports the results of wake surveys of an athlete in single and tandem formations in the Monash Wind Tunnel. Flow measurements were phase averaged over segments of the crank cycle to investigate the dynamic evolution of the wake of a pedalling cyclist. Results show that the dominant hip vortices previously identified in the wake of a single cyclist remain dominant in the trailing cyclist wake, with minimal reduction in vorticity. Wake profiles indicate the large drag saving experienced by a trailing cyclist are not due to disruption of the wake vortices or significant streamwise momentum recovery.